2020
DOI: 10.1038/s41598-020-59287-7
|View full text |Cite
|
Sign up to set email alerts
|

Remote biosensor for the determination of trypsin by using nanoporous anodic alumina as a three-dimensional nanostructured material

Abstract: tabrizi, Josep ferré-Borrull & Lluis f. Marsal * the determination of trypsin in the human real sample is a routine medical investigation to assess the pancreatic disease. Herein, we fabricated an interferometric reflectance spectroscopy based biosensor for the determination trypsin. For this purpose, urease and fluorescein 5(6)-isothiocyanate (FLITC) were immobilized on the nanoporous anodic alumina (NAA). The operation principle of the proposed biosensor is based on the change in the pH of the solution durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…In addition, an aptamer padding proved to be a valuable solution [209]. Works of Tabrizi et al show vast versatility of such structures that are capable of the precise recognition of specific biomolecules and ions: determination of lead (II) ions [210], quantitative detection of trypsin [211], or Salmonella sensing through the recognition of specific DNA fragments [212] were reported. These systems are often based on simple principles, yet providing impressive effectivity-often employing precision and selectivity of biomolecules.…”
Section: Sensorsmentioning
confidence: 99%
“…In addition, an aptamer padding proved to be a valuable solution [209]. Works of Tabrizi et al show vast versatility of such structures that are capable of the precise recognition of specific biomolecules and ions: determination of lead (II) ions [210], quantitative detection of trypsin [211], or Salmonella sensing through the recognition of specific DNA fragments [212] were reported. These systems are often based on simple principles, yet providing impressive effectivity-often employing precision and selectivity of biomolecules.…”
Section: Sensorsmentioning
confidence: 99%
“…Although the urine affected both the baseline PL of SWCNTs and the extent of the fluorescence response, we have demonstrated that our biosensor can detect trypsin and differentiate between trypsin concentrations. Recent studies have reported the development of trypsin biosensors with a limit of detection of 8.6 ng/mL using a quartz crystal microbalance (QCM) [ 59 ] and 60 ng/mL using interferometric reflectance spectroscopy (IRS) [ 58 ] under the optimum conditions. Although the minimal tested trypsin concentration in this work was 1 μg/mL, we assume that after further careful optimization, the sensitivity could be significantly enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that trypsin levels in serum and urine are dramatically increased during acute pancreatitis. While the normal range of trypsin concentration in the serum of a healthy person is 0.25 ± 0.1 μg/mL [ 56 ] and in the urine is about 115 to 350 ng/mL, patients with pancreatitis show maximum levels of 1.4 ± 0.6 [ 57 ] and 84.4 µg/mL, respectively [ 58 ]. One of the most frequently used methods for quantitative detection of proteins is enzyme-linked immunosorbent assay (ELISA) [ 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the results also demonstrated that the catalytic activity of the urease enzyme in the presence of trypsin as the protease enzyme would change [ 156 ]. In the presence of trypsin, the activity of urease decreased and the amount of the catalyzed urea to hydroxide ion and carbon dioxide decreased.…”
Section: Biosensors (Biorecognizer-based Sensors)mentioning
confidence: 99%